Misticismo e apofaticidade em A Nuvem do Não-Saber de um escritor anônimo do século XIV - Chadan, José Paulo Coelho Faradji (2013)
The dissertation wich the reader has in its hands concerns my master dissertation about the contemplation in the Cloud of Unknowing. The Cloud of Unknowing belongs to the late medieval period (XIV century), and was probably written by a cartusian monk, as a method of teaching a young man, probably around twenty-four years old, about the contemplative life. In his writing, the author compares the contemplative life to two important biblical figures. First he compares it to Mary, that having received Jesus in her house, listens to him patiently, unlike Martha, her sister, that goes about preparing his supper. Next the author compares contemplative life, to Moses, wich with a lot of effort, climbs to the top of the mountain and sees a great cloud. Mary´s passage reports to the gospel according to Luque chapter 10, verse 38-42. Moses passage belongs to the book of Exodus, chapter 24. Mary is compared to her sister Martha. The first one represents the contemplative life, while the second one represents an active life. Moses is compared to Aaron, the last one representing a person wich with little effort and by divine grace contemplates the lord, while the first one is only capable of the same with a lot of effort. We approach the degrees of ascension to the contemplative life: the purgative path; the progressive and the contemplative one. The first degree refers to the active life while the second one refers to the active and contemplative lifes. In its turn the third level relates only to the contemplative life. The active life, being the path lived according the works of mercy and charity, as well as contemplation. Is the search of the spirit becoming closer to God through silence, solitude and loving desire